A full-stress technique for structural shape optimization - Herskovits, Jose; Dias, Gilberto P.; Mota Soares, Cristovao M. (Zielona Góra: Uniwersytet Zielonogórski)
A technique for shape optimization based on a generalization of the Full-Stress Design approach is presented. Full-stress procedures for trusses design are based on the assumption that in an optimal structure each member is subjected to its allowable stress under at least one loading condition.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka